Endocrine side effects of immune checkpoint inhibitors - Cardona, Zulma; Sosman, Jeffrey A.; Chandra, Sunandana; Huang, Wenyu (Frontiers in Endocrinology, 2023)
Immune checkpoint inhibitors (ICIs) have been increasingly the mainstay of treatment of various malignancies with success. However, due to their association with autoimmunity, ICIs have resulted in a variety of side effects that involve multiple organs including the endocrine system. In this review article, we describe our current understanding of the autoimmune endocrinopathies as a result of the use of ICIs. We will review epidemiology, pathophysiology, clinical presentation, diagnosis and management of the most commonly encountered endocrinopathies including thyroiditis, hypophysitis, Type 1 diabetes, adrenalitis, central diabetes insipidus.